2009
DOI: 10.1007/s10388-009-0198-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the feasibility and safety of immediate extubation after esophagectomy with extended radical three-field lymph node dissection for thoracic esophageal cancers

Abstract: Evaluation of the feasibility and safety of immediate extubation after esophagectomy with extended radical three-fi eld lymph node dissection for thoracic esophageal cancers Abstract Background. No standard procedure exists in respiratory management, including mechanical ventilation, which is commonly administered, after thoracic esophagectomy for esophageal cancer. Methods. Various perioperative clinical parameters and complications were retrospectively compared between the patients who underwent mechanical v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…The last search was carried out in January 2021 and reached 1674 articles. After that, 38 articles were selected by title and abstract, and five were selected for full-text analysis [16][17][18][19][20] (see Figure 1). All included studies were observational.…”
Section: Baseline Characteristics Of Included Studies and Patientsmentioning
confidence: 99%
“…The last search was carried out in January 2021 and reached 1674 articles. After that, 38 articles were selected by title and abstract, and five were selected for full-text analysis [16][17][18][19][20] (see Figure 1). All included studies were observational.…”
Section: Baseline Characteristics Of Included Studies and Patientsmentioning
confidence: 99%
“…Several reports have shown that immediate extubation (IE) after McKeown esophagectomy is feasible and safe. Toh et al demonstrated that IE tended to reduce the incidence of pulmonary complications compared with VM (12% vs. 24%, NS) [18]. Imai et al reported that the rate of ambulation on POD 1 was significantly higher in the IE group than in the VM group (50 vs. 19%, p = 0.003) which resulted in a shorter ICU stay [3 (2.75-3) days vs. 3 (3-4) days, p = 0.01], without increasing postoperative complications [19].…”
Section: Discussionmentioning
confidence: 99%
“…Implementation of the ERAS protocol after esophagectomy was successful with respect to complications, postoperative hospital stay, and costs [8,[11][12][13][14][15][16][17][18][19][20][21][22]25]. In addition, postoperative EN after thoracoscopic esophagectomy was more favorable than total parental nutrition for bodyweight loss (-2.94 ± 3.19% vs. 5.05 ± 3.65%, P = 0.020) [26].…”
Section: Discussionmentioning
confidence: 99%
“…Only one study evaluated IE and MV after transthoracic esophagectomy with radical 3-field lymph node dissection. Toh et al, compared IE in the operating room and management of MV shortly after esophagectomy (average length of MV = 9.9 h) in patients after transthoracic esophagectomy with 3-field lymphadenectomy [18]. They demonstrated that the early postoperative clinical course was similar between the 2 groups.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, overnight MV is routinely carried out with the use of sedatives, which have the potential to impede early ambulation and early recovery after esophagectomy. Although several studies have demonstrated that IE in the operating room is feasible, safe, and associated with lower morbidity for patients with thoracic esophageal cancer after transthoracic esophagectomy with radical lymphadenectomy [14][15][16][17][18], the timing of extubation after esophagectomy remains controversial, with no common practice, even among experienced centers. We hypothesized that IE would also facilitate earlier recovery after esophagectomy compared with overnight MV in patients with thoracic esophageal cancer after transthoracic esophagectomy with radical 3-field lymphadenectomy.…”
Section: Introductionmentioning
confidence: 99%